Second Five Year Plan Bombay State Budget Provision for Schemes Included in the Development Programme 1957-58 - Planning Commission (Planning Commission, 1957)
This brochure is primarily intended for reference regarding the financial provision made for each scheme included in the State Plan. A general idea of the Development Programme of the Bombay State for 1957-58 was given in “Draft Development Programme for 1957-58 Bombay State’’ published in March 1957.
Government of Bombay, Political and Services Department